Nomograms in urologic oncology, advantages and disadvantages. Issue 1 (January 2019) - Bandini, Marco; Fossati, Nicola; Briganti, Alberto
Abstract : Purpose of review: To critically review the current literature regarding the recently published nomograms in urologic oncology and to examine the advantages and disadvantages of their application. Recent findings: Several nomograms have been developed in the field of urologic oncology over the recent years, to improve clinical decision-making and patients counseling. In the current review, we examined 6 nomograms on prostate cancer, 9 nomograms on kidney cancer and 8 nomograms on bladder cancer that have been recently published. Most of the examined nomograms lack external validation and very few have investigated the clinical utility of any given model, as measured by its ability to improve clinical decision-making. Two studies relied on genomic classifiers and showed up to 6% improved accuracy compared with the models based only on clinical variables. However, these new tools were limited by elevated cost and scarce availability of these new biomarkers, which may represent barriers toward future use. Summary: Several nomograms have been developed in these recent years in urologic oncology. All exhibited elevated accuracy, good calibration and promising decision analyses, when they were internally validated. However, external validations and assessment of clinical utility are needed before they can be incorporated into routine clinical practice.